الھیئات الإداریة ا لمكلفة بحمایة البیئة في التشریع الجزائري - سلطاني محمد لمین (المسيلة, 2023)
تتناول هذه الدراسة الهیئات الإداریة المكلفة بحمایة البیئة في التشریع الجزائري، وذلـك مـن زاویة ومنظور قانوني بحت، والهدف من ذلك هـو معرفـة الإطـار الهیكلـي لهـذه الهیئـات سـواء كانت مركزیة أو محلیة، والوقوف على الوسائل والآلیات التي منحها المشرع الجزائـري لـلإدارة مــن اجــل حمایــة البیئــة مــن كافــة المخــاطر التــي تحــدق بهــا، وذلــك مــن خــلال دراســة القــوانین والتشــریعات التــي تــم وضــعها لحمایــة البیئــة مــن كــل أشــكال ومصــادر التلــوث، ومعرفــة مــا إذا كانت هذه الهیئات والإجراءات كافیة لتحقیـق الهـدف الـذي أنشـئت مـن اجلـه، وبالتـالي الحفـاظ على التوازن بین البیئة والتنمیة المستدامة . الكلمات المفتاحیة: الهیئات الإداریة – حمایة البیئة – التشریع الجزائري Summary of the study: This study deals with the administrative bodies responsible for environmental protection in the Algerian legislation, from a purely legal perspective and angle. The aim is to know the structural framework of these bodies, whether they are central or local, and to examine the means and mechanisms that the Algerian legislator has given to the administration in order to protect the environment from all the risks that threaten it. This is done by studying the laws and legislations that have been put in place to protect the environment from all forms of and sources of pollution, and to know whether these bodies and procedures are sufficient to achieve the goal for which they were established, and thus maintain the balance between the environment and sustainable development. Keywords: Administrative - Bodies - Environmental – Algerian legislation 71
Keywords: الهیئات الإداریة – حمایة البیئة – التشریع الجزائري